2003
DOI: 10.1016/s0014-5793(03)00330-2
|View full text |Cite
|
Sign up to set email alerts
|

Lysenin, a unique sphingomyelin‐binding protein

Abstract: Sphingomyelin plays complex structural and signaling functions in the plasma membrane. Of special interest is that hydrolysis of sphingomyelin to ceramide can modulate dynamics of membrane rafts, which serve as signaling platforms for various receptors. This review is focused on a recently discovered sphingomyelin-binding protein, lysenin, which can be used as a unique probe to trace distribution and turnover of sphingomyelin in cellular membranes. We analyze the primary and secondary structures of lysenin wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…Lysenin comprises a family of proteins together with lysenin-related proteins 1 and 2 (14,16,55). Recently we have shown that lysenin recognizes SM in a distribution-dependent manner (15).…”
Section: Discussionmentioning
confidence: 99%
“…Lysenin comprises a family of proteins together with lysenin-related proteins 1 and 2 (14,16,55). Recently we have shown that lysenin recognizes SM in a distribution-dependent manner (15).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomyelin levels were also assessed by the binding of lysenin, a protein with high specificity for sphingomyelin, to cell membranes (28,29). KMA-positive (ARH-77_100 and JJN-3 cells) and -negative cell lines (ARH-77_neg and NCI-H929 cells) were incubated with biotinylated lysenin followed by staining with streptavidin-allophycocyanin.…”
Section: Kma Expression Is Sphingomyelin Dependentmentioning
confidence: 99%
“…To answer this question, we focused our attention on lysenin, a 297 amino acid PFT extracted from Eisenia foetida, which inserts hexameric pores (∼3 nm diameter) in artificial and natural lipid membranes containing sphingomyelin (SM) [41][42][43][44][45]. Several remarkable features make lysenin an excellent candidate for such studies.…”
Section: Introductionmentioning
confidence: 99%